An improved lifting line model for the design of marine propellers - Çelik, F; Güner, M (SOC NAVAL ARCH MARINE ENG, 2006)
This paper describes a procedure for the design of marine propellers where more realistic representation of the slipstream shape by the trailing vortex system is taken into account. The slipstream shape behind the propeller is allowed to deform and to align with the direction of local velocity, which is obtained by the sum of the inflow velocity and induced velocities due to the trailing vortices. In classical lifting line approaches, that deformation is neglected. Applications for an autonomous underwater vehicle (AUV) and a fishing vessel are carried out to demonstrate propeller design and the effect of the slipstream contraction. Furthermore, a computational fluid dynamics (CFD) analysis based on the finite volume method and experimental validation of the method are carried out for the propellers. CFD analysis and experimental results are compared with the results obtained from present method.
Keywords: Engineering; Oceanography